Composition for polishing

The polishing composition, featuring colloidal silica and an alkali metal salt in an alkaline solution, addresses the issues of residual polysilicon and recess formation by enhancing the polishing reaction, resulting in improved surface finish and reduced defects.

JP2025057133AActive Publication Date: 2025-04-09FUJIMI INCORPORATED
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023166812
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

Conventional polishing compositions often result in overpolishing of polysilicon buried within silicon dioxide recesses, leading to residual polysilicon and recess formation, even when the selectivity ratio is controlled.

Method used

A polishing composition comprising colloidal silica, an alkali metal salt, and water, with a pH of 9.0 to 11.5, is used to polish a structure with a recessed first layer and a buried second layer. The colloidal silica has a specific silanol group count and is used to accelerate the polishing reaction, reducing residual polysilicon and suppressing recess formation.

Benefits of technology

The proposed polishing composition effectively reduces residual polysilicon and suppresses recess formation, achieving improved polishing results by optimizing the pH and silanol group density of the colloidal silica.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025057133000001_ABST
    Figure 2025057133000001_ABST
Patent Text Reader

Abstract

To provide a novel composition for polishing which reduces a residual polishing target such as polysilicon to be polished and is also capable of suppressing recesses.SOLUTION: A composition for polishing, which contains colloidal silica, alkali metal salt and water, and of which the pH is 9.0 to 11.5, is used in a polishing target 10 including a first layer 1 in which a recess is provided and a second layer 2 formed so as to fill the inside of the recess, used for a step of exposing the first layer 1 by polishing the second layer 2. The first layer 1 is selected from among layers each having an oxygen-silicon bond or a nitrogen-silicon bond. The second layer has a silicon-silicon bond and or a silanol group number of the colloidal silica ranges from 6 / nm2 or more to 22 / nm2 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing composition. [Background technology]

[0002] In the field of CMP, a silicon dioxide film having a recess is disposed on top of a polysilicon film formed to fill the recess, and polishing is sometimes performed using the silicon dioxide film as a stopper layer.

[0003] The selectivity, which is the ratio of the rate at which the polysilicon film is polished to the rate at which the silicon dioxide film is polished, is used as an index of how easily the polysilicon film is polished relative to the silicon dioxide film. This is calculated by dividing the rate at which the polysilicon film is polished by that of the silicon dioxide film. In order for the silicon dioxide film to function as a stopper layer, it is better for the selectivity to be large.

[0004] Patent Document 1 provides a polishing composition that has an objective of providing a polishing composition that can obtain a large selectivity ratio and causes little surface defects, and that contains an abrasive such as silicon dioxide and water, and may further contain a basic organic compound such as tetramethylammonium hydroxide. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 10-321569 Summary of the Invention [Problem to be solved by the invention]

[0006] In the process of developing a new polishing composition, the inventors discovered that in conventional techniques, polysilicon buried in recesses formed by a silicon dioxide film is also over-polished, which can cause so-called recesses. In the process of further investigation, the inventors discovered that even if the selectivity is controlled, if the abrasive grains are not appropriate or the pH of the polishing composition is not appropriate, polysilicon remains after polishing or recesses occur.

[0007] Therefore, an object of the present invention is to provide a novel polishing composition which can reduce the amount of residue of an object to be polished, such as polysilicon, and can also suppress recesses. [Means for solving the problem]

[0008] One aspect of the present invention is a polishing composition containing colloidal silica, an alkali metal salt, and water and having a pH of 9.0 to 11.5, the composition being used in a step of polishing a first layer having a recess and a second layer formed so as to fill the recess to expose the first layer, the first layer being selected from those having an oxygen-silicon bond or those having a nitrogen-silicon bond, and the second layer having a silicon-silicon bond, and / or (ii) the number of silanol groups in the colloidal silica is 6 / nm or less. 2 More than 22 pieces / nm 2 The polishing composition is as follows: Effect of the Invention

[0009] According to the present invention, it is possible to provide a novel polishing composition which can reduce the amount of residue of an object to be polished, such as polysilicon, and also suppress recesses. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of an object to be polished before polishing. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a polished object after ideal polishing. [Diagram 3] FIG. 3 is a schematic cross-sectional view of a polished object that has not been ideally polished and has a recess as a defect. [Figure 4] FIG. 4 is a schematic cross-sectional view of a polished object in which defects that should be polished but are not ideally polished remain. [Diagram 5] FIG. 5 is a schematic cross-sectional view of a ground object showing the defects of FIG. 3 and FIG. 4 occurring simultaneously. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. In this specification, "X to Y" means "X or more and Y or less", with the numerical values ​​(X and Y) described before and after it being included as the lower and upper limits. When "X to Y" are described multiple times, for example, when "X1 to Y1 or X2 to Y2" is described, the disclosure with each numerical value as the upper limit, the disclosure with each numerical value as the lower limit, and the combination of the upper and lower limits are all disclosed (that is, they are a legitimate basis for amendment). Specifically, amendments with X1 or more, amendments with Y2 or less, amendments with X1 or less, amendments with Y2 or more, amendments with X1 to X2, amendments with X1 to Y2, etc. must all be deemed legitimate. In addition, when features or aspects of the present disclosure are described in terms of a Markush group, a person skilled in the art will recognize that the present disclosure is thereby described in terms of any individual component or subgroup of components of the Markush group.

[0012] <Polishing composition> One aspect of the present invention is a polishing composition containing colloidal silica, an alkali metal salt, and water and having a pH of 9.0 to 11.5, the composition being used in a step of polishing a first layer having a recess and a second layer formed so as to fill the recess to expose the first layer, the first layer being selected from those having an oxygen-silicon bond or those having a nitrogen-silicon bond, and the second layer having a silicon-silicon bond, and / or (ii) the number of silanol groups in the colloidal silica is 6 / nm or less. 2 More than 22 pieces / nm 2 The polishing composition is as follows. This embodiment can provide a novel polishing composition that can reduce the amount of the polished object such as polysilicon remaining and also suppress recesses. The mechanism by which such a technical effect is realized is considered to be as follows. In the alkaline pH range, hydroxide ions (OH - ) becomes rich, and the surface of the polishing object having silicon-silicon bonds such as polysilicon changes to silanol groups (SiOH). During polishing, the reaction between the polishing object converted to silanol groups (SiOH) and colloidal silica having the number of silanol groups in the above range is promoted by hydrogen bonding, reducing the residue on the pattern wafer. In addition, it is presumed that the use of an alkali metal salt suppresses excessive etching of the polishing object having silicon-silicon bonds, and as a result, is effective in suppressing recesses. However, such a mechanism is merely speculation, and the technical scope of the present invention is not limited by such a mechanism.

[0013] In one embodiment of the present invention, the method further includes a step of polishing the first layer after the first layer is exposed. By including such a step, a technical effect of completely removing the remaining part of the polishing object to be polished, such as polysilicon, is obtained.

[0014] [Abrasive grain] The polishing composition according to one embodiment of the present invention contains colloidal silica as abrasive grains. The abrasive grains have the function of mechanically polishing an object to be polished. Colloidal silica can be produced by a sol-gel method. For example, it can be obtained by carrying out a hydrolysis-condensation reaction using a hydrolyzable silicon compound (e.g., alkoxysilane or a derivative thereof) as a raw material.

[0015] According to one embodiment of the present invention, the number of silanol groups in the colloidal silica is 6 / nm 2 More than 22 pieces / nm 2 The number of silanol groups in colloidal silica is 6 / nm 2 Less than 22 particles / nm 2 If the number of silanol groups in the colloidal silica is more than 6 / nm, there is a risk that the amount of the material to be polished, such as polysilicon, remaining may increase, or recesses may be promoted. 2 More than 22 pieces / nm 2 An example of a method for controlling the amount of colloidal silica is hydrothermal treatment of a dispersion containing colloidal silica. The hydrothermal treatment conditions are, for example, heating the dispersion containing colloidal silica at a temperature of 100° C. to 200° C. for 30 to 60 minutes.

[0016] According to one embodiment of the present invention, the number of silanol groups in the colloidal silica is 6.1 / nm 2 More than 6.2 pieces / nm 2 More than 6.3 pieces / nm 2 More than 6.4 pieces / nm 2 More than 6.5 pieces / nm 2 More than 6.6 pieces / nm 2 More than 6.6 pieces / nm 2 Super, 6.7 pieces / nm 2 More than 6.8 pieces / nm 2 More than 6.9 pieces / nm 2 More than 7.0 pieces / nm 2 More than 7.1 pieces / nm 2 More than 7.2 pieces / nm 2 More than 7.3 pieces / nm 2 More than 7.4 pieces / nm 2 More than 7.5 pieces / nm 2 More than 7.6 pieces / nm2 More than 7.7 pieces / nm 2 More than 7.8 pieces / nm 2 More than 9 pieces / nm 2 More than 10 pieces / nm 2 More than 12 pieces / nm 2 More than 14 pieces / nm 2 or more than 16 / nm 2 That's all.

[0017] According to one embodiment of the present invention, the number of silanol groups in the colloidal silica is 21 / nm 2 Below, 20 pieces / nm 2 Below, 19 pieces / nm 2 Below, 18 pieces / nm 2 Below, 17.5 pieces / nm 2 Less than 17 / nm 2 Below, 16 pieces / nm 2 Below, 15 pieces / nm 2 Below, 14 pieces / nm 2 Below, 13 pieces / nm 2 Below, 12 pieces / nm 2 Below, 11 pieces / nm 2 Below, 10 pieces / nm 2 Below, 9 pieces / nm 2 Below, 8 pieces / nm 2 or less than 7 / nm 2 The number of silanol groups was measured according to the method described in the Examples.

[0018] According to one embodiment of the present invention, the pulsed NMR specific surface area of ​​the colloidal silica is 40 m 2 According to one embodiment of the present invention, the pulsed NMR specific surface area of ​​the colloidal silica is 39 m 2 / g or less, 38m 2 / g or less, 37m 2 / g or less, 36m 2 / g or less, 35m 2 / g or less, 34m 2 / g or less, 33m 2 / g or less, 32m 2 / g or less, 31m 2 / g or less, 30m 2 / g or less, 29m 2 / g or less, 28m2 / g or less, 27m 2 / g or less, 26m 2 / g or less, 25m 2 / g or less, or 24m 2 According to one embodiment of the present invention, pulsed NMR of colloidal silica is performed at 10 2 / g or more, 15m 2 / g or more, or 20m 2 / g or more. The pulse NMR specific surface area of ​​the abrasive grains (particularly colloidal silica) is measured by the method described in the Examples. The pulse NMR specific surface area of ​​colloidal silica can be controlled by increasing or decreasing the number of protons in the functional groups on the surface of the colloidal silica, in order to measure the manner in which the relaxation rate of proton resonance changes depending on the amount of molecules adsorbed on the solid surface, etc.

[0019] According to one embodiment of the present invention, the lower limit of the average primary particle size of the abrasive grains (particularly colloidal silica) is 60 nm or more, 70 nm or more, more than 70 nm, 71 nm or more, 72 nm or more, 73 nm or more, 74 nm or more, 75 nm or more, 76 nm or more, 77 nm or more, 78 nm or more, 79 nm or more, 80 nm or more, 81 nm or more, 82 nm or more, 83 nm or more, 84 nm or more, 85 nm or more, 86 nm or more, 87 nm or more, 88 nm or more, 89 nm or more, or 95 nm or more.

[0020] According to one embodiment of the present invention, the upper limit of the average primary particle size of the abrasive grains (particularly colloidal silica) is 110 nm or less, less than 100 nm, 99 nm or less, 98 nm or less, 97 nm or less, 96 nm or less, 95 nm or less, 94 nm or less, 93 nm or less, 92 nm or less, or 91 nm or less. According to one embodiment of the present invention, the average primary particle size of the colloidal silica is more than 70 nm and less than 100 nm. The average primary particle size is measured by the method described in the Examples.

[0021] According to one embodiment of the present invention, the lower limit of the average secondary particle diameter of the abrasive grains (particularly colloidal silica) is 110 nm or more, 120 nm or more, 130 nm or more, 140 nm or more, 150 nm or more, 160 nm or more, 170 nm or more, 180 nm or more, 190 nm or more, 200 nm or more, 210 nm or more, or 215 nm or more.

[0022] According to one embodiment of the present invention, the upper limit of the average secondary particle size of the abrasive grains (particularly colloidal silica) is 350 nm or less, 340 nm or less, 330 nm or less, 320 nm or less, 310 nm or less, 300 nm or less, 290 nm or less, 280 nm or less, 270 nm or less, 260 nm or less, 250 nm or less, 240 nm or less, 230 nm or less, or 225 nm or less. The average secondary particle size is measured by the method described in the Examples.

[0023] According to one embodiment of the present invention, the average degree of association (average secondary particle size / average primary particle size) of the abrasive grains (particularly colloidal silica) is 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, 2.0 or more, 2.1 or more, 2.2 or more, 2.3 or more, or 2.4 or more.

[0024] According to one embodiment of the present invention, the average degree of association (average secondary particle size / average primary particle size) of the abrasive grains (particularly colloidal silica) is 4.6 or less, 4.4 or less, 4.2 or less, 4.0 or less, 3.8 or less, 3.6 or less, 3.4 or less, 3.2 or less, 3.0 or less, 2.9 or less, 2.8 or less, 2.7 or less, 2.6 or less, or 2.5 or less.

[0025] According to one embodiment of the present invention, the content of abrasive grains (particularly colloidal silica) in the polishing composition is 0.01 mass% or more, 0.05 mass% or more, 0.1 mass% or more, 0.5 mass% or more, 0.6 mass% or more, 0.7 mass% or more, 0.8 mass% or more, 0.9 mass% or more, 1.0 mass% or more, 1.1 mass% or more, 1.2 mass% or more, 1.3 mass% or more, or 1.4 mass% or more.

[0026] According to one embodiment of the present invention, the content of abrasive grains (particularly colloidal silica) in the polishing composition is 10 mass % or less, 5 mass % or less, 3 mass % or less, or 2 mass % or less.

[0027] According to one embodiment of the present invention, the colloidal silica of the abrasive grains contained in the polishing composition is 90 mass% or more, 95 mass% or more, 98 mass% or more, 99 mass% or more, 99.5 mass% or more, or 99.9 mass% or more (the upper limit is 100 mass%).

[0028] According to one embodiment of the present invention, the surfaces of the abrasive grains (particularly colloidal silica) contained in the polishing composition have not been treated to chemically bond a treating agent such as an organic acid (e.g., a sulfonic acid).

[0029] [Alkali metal salts] The polishing composition according to one embodiment of the present invention contains an alkali metal salt. If the polishing composition does not contain an alkali metal salt, there is a risk that the amount of remaining material to be polished, such as polysilicon, cannot be reduced or that recessing is promoted.

[0030] According to one embodiment of the present invention, the alkali metal salt contains at least one of an alkali metal hydroxide and an alkali metal carbonate. According to one embodiment of the present invention, the alkali metal salt contains an alkali metal hydroxide. According to one embodiment of the present invention, the alkali metal hydroxide contains potassium hydroxide. Examples of the alkali metal include potassium, sodium, and lithium, and among them, potassium is particularly preferred from the viewpoint of reducing the amount of residual metal.

[0031] The alkali metal salt also functions as a pH adjuster that adjusts the pH of the polishing composition. According to one embodiment of the present invention, the content of the pH adjuster (particularly the alkali metal salt) contained in the polishing composition is an appropriate amount for adjusting the polishing composition to a predetermined pH (particularly a pH of 9.0 to 11.5).

[0032] According to one embodiment of the present invention, the pH adjuster contained in the polishing composition is 90% by mass or more, 95% by mass or more, 98% by mass or more, 99% by mass or more, 99.5% by mass or more, or 99.9% by mass or more (upper limit: 100% by mass). According to one embodiment of the present invention, the pH adjuster contained in the polishing composition is 90% by mass or more, 95% by mass or more, 98% by mass or more, 99% by mass or more, 99.5% by mass or more, or 99.9% by mass or more (upper limit: 100% by mass). Note that even if the abrasive grains (particularly colloidal silica) and the preservative that may be optionally contained have a function of slightly changing the pH of the polishing composition, their ability to change the pH is low, so in the present invention, they (these) are not included in the category of pH adjusters.

[0033] [pH] The pH of the polishing composition according to one embodiment of the present invention is 9.0 to 11.5. If the pH of the polishing composition is less than 9.0 or exceeds 11.5, the amount of the polished object to be polished, such as polysilicon, remaining may not be reduced, or recessing may be promoted.

[0034] According to one embodiment of the present invention, the pH of the polishing composition is 9.1 or more, 9.2 or more, 9.3 or more, 9.4 or more, 9.5 or more, more than 9.5, 9.6 or more, 9.7 or more, 9.8 or more, 9.9 or more, or 10.5 or more. According to one embodiment of the present invention, the pH of the polishing composition is 11.5 or less, 11.4 or less, 11.3 or less, 11.2 or less, 11.1 or less, 11 or less, less than 11, 10.9 or less, 10.8 or less, 10.7 or less, 10.6 or less, 10.5 or less, 10.4 or less, 10.3 or less, 10.2 or less, 10.1 or less, or 9.8 or less.

[0035] According to one embodiment of the present invention, the pH of the polishing composition is not 9.1, 9.2, 9.3, 9.4, 9.6, 9.7, 9.8, 9.9, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9, 11.1, 11.2, 11.3, 11.4, or 11.5. The pH of the polishing composition is measured according to the method described in the Examples.

[0036] [Polished object] According to one embodiment of the present invention, the polishing composition is used in a step of polishing a first layer having a recess and a second layer formed so as to fill the recess to expose the first layer. FIG. 1 is a schematic cross-sectional view of an object to be polished (before polishing). As shown in the upper diagram of FIG. 1, a first layer 1 (a film having an oxygen-silicon bond or a nitrogen-silicon bond) is formed on an arbitrary film (e.g., a Si substrate) so as to provide a recess. Then, as shown in the lower diagram of FIG. 1, a second layer 2 (a film having a silicon-silicon bond) is formed so as to fill the recess, thereby forming an object to be polished 10 including a first layer and a second layer.

[0037] When the polishing composition of the present invention is applied to such an object to be polished 10, as shown in FIG. 2, the polished object to be polished 10', which is the object to be polished after polishing, has an ideal polished surface in which the remaining part of the object to be polished (film having silicon-silicon bonds) is reduced (no remaining) and recesses are suppressed (no occurrence). In addition, by applying the polishing composition of the present invention, the number of metal atoms that may remain after polishing can also be reduced. According to one embodiment of the present invention, when the polished object to be polished is polished to a thickness of 1 cm, the polished object to be polished 10' has an ideal polished surface in which the remaining part of the object to be polished (film having silicon-silicon bonds) is reduced (no remaining). 2 The number of metal atoms remaining per unit (unit: × 10 10 pieces / cm 2 ) is 40 or less, less than 38, less than 35, 30 or less, 25 or less, 20 or less, or less than 19. According to one embodiment of the present invention, 2 The number of metal atoms remaining per unit (unit: × 10 10 pieces / cm 2) is, for example, 0, 0.01 or more, 0.5 or more, 1 or more, 5 or more, or 10 or more. When an object to be polished 10 including a first layer and a second layer is polished with a polishing composition other than the polishing composition of the present invention (i.e., a comparative polishing composition), for example, a recess 2a is generated as shown in FIG. 3, or a remaining portion 2b of the object to be polished (a film having silicon-silicon bonds) is generated as shown in FIG. 4, or these are generated simultaneously as shown in FIG. 5.

[0038] In one embodiment of the present invention, examples of the object to be polished having oxygen-silicon bonds include TEOS type silicon oxide (hereinafter also simply referred to as "TEOS") produced using tetraethyl orthosilicate as a precursor, HDP (High Density Plasma), USG (Undoped Silicate Glass), PSG (Phosphorus Silicate Glass), BPSG (Boron-Phospho Silicate Glass), RTO (Rapid Thermal Oxidation), etc. The TEOS film can be formed by plasma CVD.

[0039] In one embodiment of the present invention, examples of the polishing object having a nitrogen-silicon bond include a silicon nitride film or SiCN (silicon carbonitride). Among these, it is preferable that the first layer is a silicon oxide film derived from tetraethyl orthosilicate (TEOS film). In one embodiment of the present invention, examples of the polishing object having a silicon-silicon bond include polysilicon, amorphous silicon, single crystal silicon, n-type doped single crystal silicon, p-type doped single crystal silicon, Si-based alloys such as SiGe, etc. Among these, it is preferable that the second layer is polycrystalline silicon such as polysilicon.

[0040] [Polishing speed] According to one embodiment of the present invention, the polishing composition has physical properties that provide a polishing rate for the second layer of 2000 Å / min or more, 2200 Å / min or more, 2400 Å / min or more, 2600 Å / min or more, 2800 Å / min or more, or 3000 Å / min or more. According to one embodiment of the present invention, the polishing composition has physical properties that provide a polishing rate for the second layer of 3500 Å / min or less, or 3200 Å / min or less.

[0041] According to one embodiment of the present invention, the polishing composition has physical properties that provide a polishing rate for the first layer of 60 Å / min or more, 70 Å / min or more, 80 Å / min or more, or 90 Å / min or more. According to one embodiment of the present invention, the polishing composition has physical properties that provide a polishing rate for the first layer of 180 Å / min or less, 160 Å / min or less, 140 Å / min or less, 120 Å / min or less, 100 Å / min or less, or 95 Å / min or less.

[0042] [Selection ratio] According to one embodiment of the present invention, the polishing composition has physical properties such that the polishing rate of the second layer relative to the polishing rate of the first layer (selectivity ratio) is 17 to 40, or 20 to 40. If the selectivity ratio is less than 17 or more than 40, there is a risk that the amount of remaining material to be polished, such as polysilicon, cannot be reduced or that recessing is promoted.

[0043] According to one embodiment of the present invention, the polishing composition has physical properties such that the selectivity is 17 or more, 18 or more, 19 or more, 20 or more, 21 or more, 22 or more, 23 or more, 24 or more, 25 or more, 26 or more, 27 or more, 28 or more, 29 or more, 30 or more, 31 or more, 32 or more, 33 or more, 34 or more, or 35 or more.

[0044] According to one embodiment of the present invention, the polishing composition has physical properties such that the selectivity is 39 or less, 37 or less, 35 or less, 33 or less, 31 or less, or 29 or less.

[0045] [Transmittance] According to one embodiment of the present invention, when the concentration of abrasive grains (particularly colloidal silica) contained in the polishing composition is 1.5 mass %, the transmittance of the polishing composition when light having a wavelength of 450 nm is transmitted through the polishing composition is more than 0.1% and less than 1%. According to this embodiment, by improving the mechanical action on the object to be polished, such as polysilicon, it is effective in reducing residues on the pattern wafer. Methods for adjusting the transmittance to the above range include, for example, a method for adjusting the particle size of colloidal silica and a method for adjusting electrical conductivity.

[0046] According to one embodiment of the present invention, the transmittance is 0.13% or more, or 0.5% or more, According to one embodiment of the present invention, the transmittance is 0.9% or less, 0.7% or less, 0.5% or less, or 0.3% or less.

[0047] Here, when the abrasive concentration of the polishing composition is not 1.5% by mass, the abrasive concentration can be adjusted to 1.5% by mass as follows. That is, when the abrasive concentration of the polishing composition is more than 1.5% by mass, an appropriate amount of water can be added so that the abrasive concentration becomes 1.5% by mass. When the abrasive concentration of the polishing composition is less than 1.5% by mass, the polishing composition can be stored in an environment of 25 to 40°C until the abrasive concentration becomes 1.5% by mass, or a process such as ultrafiltration can be performed.

[0048] [water] The polishing composition of one aspect of the present invention contains water as an aqueous carrier. According to one embodiment of the present invention, the aqueous carrier may contain, but is not limited to, alcohols such as methanol, ethanol, ethylene glycol, etc.; ketones such as acetone, etc.; however, the aqueous carrier contains 90 mass % or more, 95 mass % or more, 98 mass % or more, 99 mass % or more, 99.5 mass % or more, or 99.9 mass % or more of water (upper limit is 100 mass %).

[0049] [Preservatives] According to one embodiment of the present invention, the polishing composition contains a preservative. Examples of the preservative include isothiazoline preservatives such as 2-methyl-4-isothiazolin-3-one and 5-chloro-2-methyl-4-isothiazolin-3-one, paraoxybenzoic acid ester preservatives such as methyl paraoxybenzoate and ethyl paraoxybenzoate, and phenoxyethanol. These preservatives may be used alone or in combination of two or more.

[0050] According to one embodiment of the present invention, the polishing composition may contain 0.001 to 1 mass %, 0.005 to 0.5 mass %, or 0.01 to 0.1 mass % of a preservative.

[0051] According to one embodiment of the present invention, the number of silanol groups is 6 / nm 2 More than 22 pieces / nm 2 There is provided a polishing composition which is substantially composed of the following colloidal silica, an alkali metal salt, a preservative, and water, and has a pH of 9.0 to 11.5.

[0052] [Other ingredients] The polishing composition of the present invention preferably has a simple composition, that is, it is preferable that the composition does not contain as many components as possible other than colloidal silica, alkali metal salt (particularly potassium hydroxide), water, and optionally contained preservatives. When the composition contains components other than colloidal silica, alkali metal salt (particularly potassium hydroxide), water, and optionally contained preservatives, the ratio of the components (the total of the components) in the polishing composition is preferably 0.1 mass% or less, 0.01 mass% or less, 0.001 mass% or less, or less than 0.0001 mass%. In the polishing composition, when the concentration of one or more components (if two or more, the total of the components) other than colloidal silica, alkali metal salt (particularly potassium hydroxide), water, and optionally contained preservatives is 0.1 mass% or less, 0.01 mass% or less, 0.001 mass% or less, or less than 0.0001 mass%, the component (the components) is also referred to as being "substantially free of".

[0053] According to one embodiment of the present invention, the polishing composition is substantially free of at least one of hydroxyethyl cellulose (HEC), polyacrylic acid (PAA), polyoxyethylene (POE) lauryl ether, dodecylbenzene sulfonic acid (DBS), hydrogen peroxide (H2O2), ammonia (ammonium ion), and amine. According to one embodiment of the present invention, the polishing composition is substantially free of polyoxyalkylene alkyl ether. According to one embodiment of the present invention, the polishing composition is substantially free of alkylaryl sulfonic acid.

[0054] According to one embodiment of the present invention, the composition is substantially free of at least any of a water-soluble polymer, a surfactant, an oxidizing agent, and a compound having a nitrogen atom.

[0055] The water-soluble polymer refers to a polymer that, when dissolved in water at a concentration of 0.5% by mass at the temperature at which the water-soluble polymer is most soluble, is filtered through a G2 glass filter (maximum pore size 40-50 μm), and the mass of insoluble matter filtered out is within 50% by mass of the water-soluble polymer added. Examples of the water-soluble polymer include nonionic water-soluble polymers such as polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), pullulan, and hydroxyethyl cellulose; anionic water-soluble polymers such as polyacrylic acid and carboxymethyl cellulose; and cationic water-soluble polymers such as polyacrylamide. According to one embodiment of the present invention, the polishing composition is substantially free of at least one of these.

[0056] A surfactant is a substance having a hydrophilic group and a hydrophobic group. Examples of the surfactant include alkyl ether type such as polyoxyethylene lauryl ether and polyoxyethylene oleyl ether, alkyl phenyl ether type such as polyoxyethylene octylphenyl ether, alkyl ester type such as polyoxyethylene laurate, alkyl amine type such as polyoxyethylene lauryl amino ether, alkyl amide type such as polyoxyethylene lauric acid amide, polypropylene glycol ether type such as polyoxyethylene polyoxypropylene ether, alkanol amide type such as oleic acid diethanol amide, and allyl phenyl ether type such as polyoxyalkylene allyl phenyl ether. Other examples of the surfactants include nonionic surfactants such as propylene glycol, diethylene glycol, monoethanolamine, alcohol ethoxylate, alkylphenol ethoxylate, tertiary acetylene glycol, and alkanolamide; anionic surfactants such as carboxylic acid type such as sodium myristate, sodium palmitate, sodium stearate, sodium laurate, and potassium laurate; sulfate ester type such as sodium octyl sulfate; phosphate ester type such as lauryl phosphoric acid and sodium lauryl phosphate; sulfonic acid type such as dioctyl sodium sulfosuccinate and sodium dodecylbenzenesulfonate; cationic surfactants such as amines such as laurylamine hydrochloride; and benign surfactants such as alkyl betaines and sulfobetaines such as lecithin, alkylamine oxide, and N-alkyl-N,N-dimethylammonium betaine. According to one embodiment of the present invention, the polishing composition is substantially free of at least one of these surfactants.

[0057] The oxidizing agent may be a substance having a higher redox potential than the redox potential of the substrate material (particularly polysilicon) at the pH at which polishing is performed. Here, the pH at which the polishing is performed is usually the same as the pH of the polishing composition. The redox potential of the substrate material may be determined by dispersing the powder of the material (particularly polysilicon) in water to form a slurry, adjusting the slurry to the same pH as the polishing composition, and then measuring the redox potential of the slurry (redox potential relative to a standard hydrogen electrode at a liquid temperature of 25°C) using a commercially available redox potentiometer. Examples of the oxidizing agent include hydrogen peroxide, metal oxides, peroxides, nitrates, iodates, periodates, hypochlorites, chlorites, chlorates, perchlorates, persulfates, dichromates, permanganates, organic oxidizing agents, ozone water, silver (II) salts, iron (III) salts, etc. According to one embodiment of the present invention, the polishing composition is substantially free of at least one of these.

[0058] Examples of compounds having nitrogen atoms include hydroxides such as tetramethylammonium, tetraethylammonium, and tetrabutylammonium, and salts such as chlorides, carbonates, sulfates, and phosphates. Specific examples include quaternary ammonium compounds such as tetraalkylammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrabutylammonium hydroxide, tetraalkylammonium hydroxide salts such as tetramethylammonium carbonate and tetramethylammonium chloride, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, monoethanolamine, N-(β-aminoethyl)ethanolamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, anhydrous piperazine, piperazine hexahydrate, 1-(2-aminoethyl)piperazine, N-methylpiperazine, and guanidine, and ammonia. According to one embodiment of the present invention, the polishing composition is substantially free of at least one of these.

[0059] According to one embodiment of the present invention, the polishing composition does not contain a polymer compound containing a lactam ring, or if it does contain one, the amount is less than 0.0001 mass %.

[0060] According to one embodiment of the present invention, the polishing composition is substantially free of abrasive grains other than colloidal silica.

[0061] According to one embodiment of the present invention, the polishing composition is substantially free of silica having acidic groups (eg, sulfo groups, carboxyl groups, phosphate groups, etc.) derived from an organic acid fixed to the surface.

[0062] According to one embodiment of the present invention, the polishing composition is substantially free of silica having amino groups fixed to the surface.

[0063] According to one embodiment of the present invention, the polishing composition is substantially free of organic acids.

[0064] In one embodiment of the present invention, the number of silanol groups is 6 / nm 2 More than 22 pieces / nm 2 A polishing composition is provided which is substantially composed of only the following colloidal silica, an alkali metal salt, and water, and has a pH of 9.0 to 11.5. The above explanations can be applied to the colloidal silica, the alkali metal salt (particularly potassium hydroxide), the water, the pH, and the preservative. "Substantially composed" means that when the polishing composition contains components other than colloidal silica, the alkali metal salt (particularly potassium hydroxide), the water, and the optionally contained preservative, the ratio of these components (the total of these components) in the polishing composition is 0.1 mass % or less, 0.01 mass % or less, 0.001 mass % or less, or less than 0.0001 mass %.

[0065] In one embodiment of the present invention, the polishing composition may be a one-liquid type or a multi-liquid type including a two-liquid type. The polishing composition of one aspect of the present invention may be used as a polishing liquid after dilution (typically diluted with water), or may be used as a polishing liquid as it is. That is, the concept of the polishing composition in the technology according to the present invention includes both a polishing composition (working slurry) that is supplied to an object to be polished and used for polishing the object to be polished, and a concentrated liquid (original liquid of working slurry) that is diluted and used for polishing. The concentration ratio of the concentrated liquid can be, for example, about 2 to 100 times on a volume basis.

[0066] <Method of manufacturing the polishing composition> In one embodiment of the present invention, the method for producing a polishing composition comprises adjusting the pH to 9.0 to 11.5 by including colloidal silica, an alkali metal salt (particularly potassium hydroxide), water, and an optional preservative. The above explanations can be applied to the colloidal silica, the alkali metal salt (particularly potassium hydroxide), water, pH, and the preservative. The temperature at which each component is mixed is not particularly limited, but is preferably 10°C or higher and 40°C or lower, and may be heated to increase the dissolution rate. The mixing time is also not particularly limited as long as the components can be mixed uniformly.

[0067] <Method of polishing the object to be polished> In one embodiment of the present invention, a method for polishing an object to be polished includes a step of polishing a first layer 1 (a layer having oxygen-silicon bonds or nitrogen-silicon bonds) having a recess formed therein and a second layer 2 (a layer having silicon-silicon bonds) formed so as to fill the recess, as shown in Fig. 1, to expose the first layer 1. In one embodiment of the present invention, the method further includes a step of polishing the first layer after the first layer is exposed. By including such a step, a technical effect is achieved in that remaining portions of the object to be polished, such as polysilicon, can be completely removed.

[0068] In one embodiment of the present invention, as shown in Fig. 1, a first layer 1 (a layer having oxygen-silicon bonds or a layer having nitrogen-silicon bonds) is formed on an arbitrary film (e.g., a Si substrate) so as to provide a recess. A second layer 2 (a film having silicon-silicon bonds) is then formed so as to fill the recess, and an excessive amount of the second layer 2 is stacked so as to protrude from the recess of the first layer 1, thereby forming a polishing object 10 including the first layer 1 and the second layer 2. Such a polishing object 10 is polished by a polishing device capable of supplying the polishing composition of the present invention.

[0069] In one embodiment of the present invention, the polishing apparatus used may be a general polishing apparatus equipped with a holder for holding a substrate or the like having an object to be polished, a motor capable of changing the rotation speed, and the like, and having a polishing platen onto which a polishing pad (polishing cloth) can be attached.

[0070] In one embodiment of the present invention, the polishing pad may be made of any material, including general nonwoven fabric, polyurethane, and porous fluororesin, without any particular limitations. The polishing pad is preferably provided with grooves for storing the polishing liquid.

[0071] In one embodiment of the present invention, the polishing conditions are, for example, preferably 10 to 500 rpm or less for the rotation speed of the polishing platen and the carrier, each independently. The pressure (polishing pressure) applied to the substrate having the object to be polished is preferably 0.5 to 10 psi. There is no particular limitation on the method of supplying the polishing composition to the polishing pad, and for example, a method of continuously supplying the composition using a pump or the like is adopted. There is no limitation on the amount of supply, but it is preferable that the surface of the polishing pad is always covered with the polishing composition of the present invention.

[0072] As shown in Figure 2, by applying the polishing composition of the present invention, the polished object 10', which is the object to be polished after polishing, has an ideal polished surface in which the amount of the object to be polished that should be polished is reduced (there is no remaining material) and recesses are suppressed (no recesses occur). EXAMPLES

[0073] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. In the following, unless otherwise specified, the operations were performed under the conditions of room temperature (25°C) and relative humidity of 40 to 50% RH.

[0074] <Production of Polishing Composition> A polishing composition was prepared by mixing abrasive grains, an alkali metal salt, and water so as to obtain the composition shown in Table 1. For example, the polishing composition of Example 1 had a pulse NMR specific surface area of ​​23.8 m 2 / g, 7.9 silanol groups / nm 2 The composition contains 1.5 mass % colloidal silica having an average primary particle size of 90 nm and an average secondary particle size of 220 nm, potassium hydroxide, and water, and has a pH of 10.

[0075] <How to calculate particle size> The average primary particle size of the abrasive grains was calculated from the specific surface area of ​​the abrasive grains measured by the BET method using a "MacsorbHM model-1210" manufactured by Mountech Co., Ltd., and the density of the abrasive grains.

[0076] The average secondary particle size of the abrasive grains was measured using a dynamic light scattering particle size / particle size distribution analyzer UPA-UT151 manufactured by Nikkiso Co., Ltd.

[0077] <How to calculate the number of silanol groups> Number of silanol groups per unit surface area of ​​abrasive grain (unit: silanol groups / nm 2 ) was calculated by the following method after each parameter was measured or calculated by the following measurement method or calculation method.

[0078] More specifically, C in the following formula is the total mass of the abrasive grains, and S in the following formula is the BET specific surface area of ​​the abrasive grains. More specifically, first, 1.50 g of abrasive grains as solid content is collected in a 200 ml beaker, 100 ml of pure water is added to make a slurry, and then 30 g of sodium chloride is added and dissolved. Next, 1N hydrochloric acid is added to adjust the pH of the slurry to 3.0 to 3.5, and pure water is added until the slurry becomes 150 ml.

[0079] The pH of this slurry is adjusted to 4.0 using an automatic titration device (HIRANUMA SANGYO CO., LTD., COM-1700) with 0.1N sodium hydroxide at 25°C, and the volume V [L] of 0.1N sodium hydroxide solution required to increase the pH from 4.0 to 9.0 by pH titration is measured. The average silanol group density (number of silanol groups) can be calculated using the following formula.

[0080] ρ = (c × V × N A ) / (C×S) In the above formula, ρ is the average silanol group density (number of silanol groups) (number / nm 2 ) ; c represents the concentration (mol / L) of the sodium hydroxide solution used in the titration; V is the volume (L) of sodium hydroxide solution required to raise the pH from 4.0 to 9.0 Represents; N A represents the Avogadro constant (units / mol); C represents the total mass (solids) of the abrasive grains (g); S is the weighted average value of the BET specific surface area of ​​the abrasive grains (nm 2 The BET specific surface area is the value of the specific surface area of ​​the abrasive grains measured by the BET method using a "MacsorbHM model-1210" manufactured by Mountech Co., Ltd.

[0081] <Method for measuring specific surface area using pulsed NMR> A sample dispersion was prepared by dispersing each abrasive grain (raw colloidal silica) in water to a concentration of 20% by mass. The specific surface area was measured under the following measurement conditions using a pulsed NMR particle interface property evaluation device (manufactured by Xigo Nanotools), and the results are shown in Table 1. Measurement conditions Bulk relaxation time: 2409ms Specific surface relaxivity:0.00026 Volume ratio of particles to liquid:0.1136.

[0082] <Measurement of pH of polishing composition> A glass electrode type hydrogen ion concentration indicator (model number: F-23, manufactured by Horiba, Ltd.) was used and three-point calibration was performed using standard buffer solutions (phthalate pH buffer solution, pH: 4.01 (25°C), neutral phosphate pH buffer solution, pH: 6.86 (25°C), carbonate pH buffer solution, pH: 10.01 (25°C)).The glass electrode was then placed in the polishing composition and the value after stabilization for more than 2 minutes was measured as the pH of the polishing composition.

[0083] <Measurement of transmittance of polishing composition> The transmittance of the polishing composition was measured by irradiating the polishing composition with light having a wavelength of 450 nm using an ultraviolet-visible spectrophotometer (UV-2450, manufactured by Shimadzu Corporation). The results are shown in Table 1.

[0084] <Measurement of polishing speed> The polishing composition was used to polish the surface of the object to be polished under the following polishing conditions. The objects to be polished were a silicon wafer (300 mm, blanket wafer) with a 5000 Å thick polysilicon (Poly-Si) film formed on its surface, and a silicon wafer (300 mm, blanket wafer) with a 10000 Å thick P-TEOS film (a TEOS film (silicon dioxide film) formed by plasma CVD) formed on its surface.

[0085] (polishing conditions) Polishing equipment: Ebara Corporation 300mm CMP single-sided polishing equipment FREX300E Pad: Nitta Haas Co., Ltd. Hard polyurethane pad IC1010 Polishing pressure: 2.2 psi (1 psi = 6894.76 Pa, same below) Polishing platen rotation speed: 70 rpm Carrier rotation speed: 70 rpm Supply of polishing composition: free-flowing Polishing composition supply amount: 200ml / min Polishing time: 60 seconds.

[0086] The polishing rate was measured by measuring the thickness with an optical film thickness meter (ASET-f5x: manufactured by KLA-Tencor Corporation) and dividing (thickness before polishing) - (thickness after polishing) by the polishing time. The ratio of the polishing rate of the polysilicon film (Å / min) to the polishing rate of the P-TEOS film (Å / min) was calculated as the selectivity. The results are shown in Table 1.

[0087] <Polysilicon recess evaluation> A patterned wafer with a polysilicon film was polished using the polishing composition under the following [Condition 1]. As shown in Figure 1, the patterned wafer was prepared by laminating a P-TEOS film (1000 Å) on a Si substrate, forming a recess by digging a trench 1000 Å deep, and then laminating a polysilicon film (2000 Å) so as to fill the recess.

[0088] The polishing of the polysilicon film-coated patterned wafer was continued for a time equivalent to 40% of the polishing time until the endpoint signal was detected after the endpoint signal was detected, and then the polishing was terminated. In this way, a process of polishing the first layer (P-TEOS film) further after the first layer (P-TEOS film) was exposed was realized.

[0089] The recess depth was measured in an isolated wiring portion having a width of 1 μm on the surface of the patterned wafer using an atomic force microscope (product name WA-1300, manufactured by Hitachi Kenki Finetech Co., Ltd.) The recess depth thus obtained was evaluated according to the following criteria.

[0090] [Condition 1] Polishing equipment: Ebara Corporation 300mm CMP single-sided polishing equipment FREX300E Pad: Nitta Haas Co., Ltd. Hard polyurethane pad IC1010 Polishing pressure: 2.2 psi (1 psi = 6894.76 Pa, same below) Polishing platen rotation speed: 70 rpm Carrier rotation speed: 70 rpm Supply of polishing composition: free-flowing Polishing composition supply amount: 200ml / min.

[0091] [Recess amount] The recess was judged according to the following four-level rating criteria. △× is not acceptable for practical use. The results are shown in Table 1.

[0092] ◎: Less than 15 nm ○: 15nm or more and less than 30nm △: 30nm or more and less than 50nm ×: 50 nm or more.

[0093] <Remaining polysilicon (polishing residue)> The thickness of the polysilicon remaining on the P-TEOS film after polishing was measured using an optical film thickness measuring device (ASET-f5x: manufactured by KLA-Tencor). The film thickness at this point was taken as the polishing residue and was judged according to the following four-level judgment criteria. △× is not acceptable for practical use. The results are shown in Table 1.

[0094] ◎: Less than 5Å ○: 5 Å or more and less than 10 Å △: 10 Å or more and less than 20 Å ×: 20 Å or more.

[0095] [Metal impurity measurement] The polished silicon wafer with P-TEOS film was washed for 60 seconds in the washing section while spraying deionized water (DIW) using a PVA brush. It was then dried for 30 seconds in a spin dryer. The concentrations of Na, K, and Li on the washed wafer surface were measured using a total reflection X-ray fluorescence analyzer (TREX-610T) manufactured by Technos Corporation. The results are shown in Table 1.

[0096] [Table 1]

[0097] <Consideration> The polishing compositions of the Examples were able to reduce the amount of polysilicon remaining to be polished and also suppress recesses, whereas the polishing compositions of the Comparative Examples caused the amount of polysilicon remaining to be polished and promoted recesses, as shown in Figs.

[0098] The polishing composition of Example 1 had the best results among all the Examples.

[0099] When polishing was performed using the polishing compositions of Examples 2 and 5, the remaining polysilicon film was slightly thicker or a slight recess was generated. From these results, it was found that the number of silanol groups in the abrasive grains (colloidal silica) was 6.6 / nm 2 Super 17.5 pieces / nm 2 It can also be seen that the average primary particle size of the abrasive grains (colloidal silica) is preferably more than 70 nm and less than 100 nm.

[0100] When polishing with the polishing composition of Example 3, the amount of sodium remaining as a metal impurity was slightly large. When polishing with the polishing composition of Example 4, the selectivity was slightly small and some recesses were generated. When polishing with the polishing composition of Example 8, the amount of lithium remaining as a metal impurity was slightly large. These results suggest that potassium hydroxide is suitable as an alkali metal salt.

[0101] When polishing was performed using the polishing composition of Example 6, the remaining polysilicon film was slightly thicker and some recesses were generated. When polishing was performed using the polishing composition of Example 7, some recesses were generated. These results suggest that the pH of the polishing composition is preferably more than 9.5 and less than 11. [Explanation of symbols]

[0102] 1 first layer, 2 second layer, 2a recess, 2b Remaining second layer to be polished 10 Object to be polished, 10' Polished object.

Claims

1. A polishing composition comprising colloidal silica, an alkali metal salt, and water, and having a pH of 9.0 to 11.5, (i) In an object to be polished, the object has a first layer having a recess and a second layer formed so as to fill the recess, the polishing method is used in a step of polishing the second layer to expose the first layer, the first layer being selected from those having an oxygen-silicon bond or a nitrogen-silicon bond, and the second layer having a silicon-silicon bond. and / or (ii) The number of silanol groups in the colloidal silica is 6 / nm 2 More than 22 pieces / nm 2 1. A polishing composition comprising:

2. 2. The polishing composition according to claim 1, wherein the polishing rate of the second layer relative to the polishing rate of the first layer is 20 to 40.

3. The colloidal silica has a pulsed NMR specific surface area of ​​40 m 2 The polishing composition according to claim 1 , wherein the polishing composition has a viscosity of 1000:1 or less.

4. 2. The polishing composition according to claim 1, wherein the average primary particle size of the colloidal silica is more than 70 nm and less than 100 nm.

5. The polishing composition according to claim 1 , wherein the alkali metal salt is an alkali metal hydroxide.

6. 6. The polishing composition according to claim 5, wherein the alkali metal hydroxide is potassium hydroxide.

7. HEC, PAA, POE lauryl ether, DBS, H 2 O 2 The polishing composition according to claim 1 , which is substantially free of at least one of ammonia and an amine.

8. 2. The polishing composition according to claim 1, which is substantially free of at least any of a water-soluble polymer, a surfactant, an oxidizing agent, and a compound having a nitrogen atom.

9. 2. The polishing composition according to claim 1, wherein when the concentration of the colloidal silica is 1.5 mass%, the transmittance when light with a wavelength of 450 nm is transmitted is more than 0.1% and less than 1%.

10. Number of silanol groups: 6 / nm 2 More than 22 pieces / nm 2 A polishing composition substantially consisting of the following colloidal silica, an alkali metal salt, and water, and having a pH of 9.0 to 11.

5.

11. Number of silanol groups: 6 / nm 2 More than 22 pieces / nm 2 A polishing composition substantially consisting of the following colloidal silica, an alkali metal salt, a preservative, and water, and having a pH of 9.0 to 11.5.

Citation Information

Patent Citations

  • Polishing composition and polishing method

    JP2015196704A

  • Polishing liquid, polishing liquid set and method for polishing substrate

    JP2017149798A

  • Polishing composition, polishing method, and method for manufacturing substrate

    JP2021080441A

  • Chemical mechanical polishing composition and polishing method

    JP2023094060A

  • Polishing liquid and chemical mechanical polishing method

    WO2019181399A1